Analysing functional implications of differences in left ventricular morphology using statistical shape modelling - Froso Sophocleous; Lucy Standen; Gemina Doolub; Reem Laymouna; Chiara Bucciarelli-Ducci; Massimo Caputo; Nathan Manghat; Mark Hamilton; Stephanie Curtis; Giovanni Biglino (Scientific Reports, 2022)
Abstract Functional implications of left ventricular (LV) morphological characterization in congenital heart disease are not widely explored. This study qualitatively and quantitatively assessed LV shape associations with a) LV function and b) thoracic aortic morphology in patients with aortic coarctation (CoA) with/without bicuspid aortic valve (BAV), and healthy controls. A statistical shape modelling framework was employed to analyse three-dimensional (3D) LV shapes from cardiac magnetic resonance (CMR) data in isolated CoA (n = 25), CoA + BAV (n = 30), isolated BAV (n = 30), and healthy controls (n = 25). Average 3D templates and deformations were computed. Correlations between shape data and CMR-derived morphometric parameters (i.e., sphericity, conicity) or global and apical strain values were assessed to elucidate possible functional implications. The relationship between LV shape features and arch architecture was also explored. The LV template was shorter and more spherical in CoA patients. Sphericity was overall associated with global and apical radial (p = 0.001, R2 = 0.09; p < 0.0001, R2 = 0.17) and circumferential strain (p = 0.001, R2 = 0.10; p = 0.04, R2 = 0.04), irrespective of the presence of aortic stenosis and/or regurgitation and controlling for age and hypertension status. LV strain was not associated with arch architecture. Differences in LV morphology were observed between CoA and BAV patients. Increasing LV sphericity was associated with reduced strain, independent of aortic arch architecture and functional aortic valve disease.